SISTEM PERDAGANGAN TRADISIONAL DALAM KOMUNITAS ORANG BUYAKA - Elvis Kabey (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2010)
The traditional trading system done by the Buyaka community who live around Sentani Lake area is by using barter. The nature products are traded with stone axes, glass beads, pottery, wooden utensils and glass bracelet. The trade is done among the Buyaka community themselves and with the people who live in coastal area.